Peusijuek as Living Fiqh: A Pre-Litigation Islah Mechanism for Domestic Conflict Resolution in Aceh - Aris Nandar; Siti Masruchah; Dzulfikar Dzulfikar (Journal of General Education and Humanities, 2026)
This research examines the practice of Peusijuek as a pre-litigation islah mechanism for resolving domestic conflicts in Pante Ceureumen District, West Aceh, Indonesia. While previous studies have primarily examined Peusijuek as a cultural tradition, they have given limited attention to its role as a normative mechanism in the interaction between customary and Islamic law. Employing a qualitative approach within an interpretive paradigm, the study collected data through in-depth interviews with nine informants, participant observation, and document analysis, which were analyzed using thematic coding. The findings reveal that Peusijuek operates as a multi-tiered mediation mechanism prior to formal litigation by integrating social, spiritual, and moral dimensions into the reconciliation process while shaping the distribution of authority among families, customary institutions, and the state. From the perspective of living fiqh, Peusijuek embodies the values of islah and maqāṣid al-sharīʿah through local customary practices. The study demonstrates that legal pluralism in Aceh is both complementary and productive, although normative ambivalence remains in cases involving domestic violence. These findings contribute to the development of Islamic family law scholarship and provide practical insights for strengthening community-based dispute resolution within legally plural societies.